Introduction to intelligence institutions, operations, and analysis - Acuff, Jonathan M.; Craft, LaMesha L.; Ferrero, Christopher J.; Fitsanakis, Joseph; Kilroy, Richard J.; Smith, Jonathan C. (CQ Press, A Division of Sage, 2022)
"Introduction to Intelligence: Institutions, Operations, and Analysis offers a strategic, international, and comparative approach to covering intelligence organizations and domestic security issues. Written by multiple authors, each chapter draws on the author's professional and scholarly expertise in the subject matter. As a core text for an introductory survey course in intelligence, this text provides a comprehensive introduction to intelligence, including institutions and processes, collection, communications, and common analytic methods"--